2021
DOI: 10.4103/iju.iju_217_21
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic solid cystic renal cell carcinoma: A series of 3 cases elucidating the spectrum of morphological and clinical features of an emerging new entity

Abstract: Eosinophilic solid cystic renal cell carcinoma (ESC-RCC) is a recently described entity, which demonstrates distinct clinical, pathological and molecular features. We present a series of three cases, the first to be reported from the Indian subcontinent. All three patients were over 50 years of age; and presented with a large kidney mass. One patient had a locally advanced disease while the other two presented with metastases. Microscopic examination revealed a tumor displaying solid-cystic and/or papillary ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…They may manifest as solid, mixed solid-cystic, or cystic lesions, depending on the proportion of the solid and cystic components. [6][7][8][9] Sakhadeo et al 6 reported a case of high-grade eosinophilic solid and cystic renal cell carcinoma with lymph node and bone metastases showing intense FDG uptake as was observed in our case. Tong et al 7 reported a case of eosinophilic solid and cystic renal cell carcinoma in bilateral kidney showing no significant FDG uptake, but increased 99m Tc-MIBI uptake mimicking oncocytoma or lipid-poor angiomyolipoma.…”
supporting
confidence: 76%
See 3 more Smart Citations
“…They may manifest as solid, mixed solid-cystic, or cystic lesions, depending on the proportion of the solid and cystic components. [6][7][8][9] Sakhadeo et al 6 reported a case of high-grade eosinophilic solid and cystic renal cell carcinoma with lymph node and bone metastases showing intense FDG uptake as was observed in our case. Tong et al 7 reported a case of eosinophilic solid and cystic renal cell carcinoma in bilateral kidney showing no significant FDG uptake, but increased 99m Tc-MIBI uptake mimicking oncocytoma or lipid-poor angiomyolipoma.…”
supporting
confidence: 76%
“…There are currently limited data regarding the imaging features of eosinophilic solid and cystic renal cell carcinoma. They may manifest as solid, mixed solid-cystic, or cystic lesions, depending on the proportion of the solid and cystic components 6–9 . Sakhadeo et al 6 reported a case of high-grade eosinophilic solid and cystic renal cell carcinoma with lymph node and bone metastases showing intense FDG uptake as was observed in our case.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…7,8 Subsequently, ESC-RCC also has been reported in younger individuals and males. 25,31,50,51 ESC-RCC is considered to be the sporadic counterpart to the third subtype (RCC with an eosinophilic cytoplasm as well as a solid and cystic growth pattern) of TSC-associated RCC. [52][53] The great majority of ESC-RCCs are sporadic, with approximately 10% occurring in patients with TSC.…”
Section: Esc-rccmentioning
confidence: 99%